STRATEGI ARAB SAUDI TERHADAP STABILITAS PEMERINTAHANNYA TAHUN 2011-2013 - Arif Wicaksana; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Middle east revolution or Arab Spring has destroyed most of middle east nations and government. The revolution carry two main factor which causing revolution. First factor is democratization issue, and Sunni-Shi’a conflict as a second factor. Saudi Arabia as a part of middle east region can’t avoid impact by revolution. On the other hand, Saudi Arabia has two main factor which causing revolution either. This research is focused to explain reasons why Saudi Arabia government could survive during the revolution and still standing as a stable government in the region.This research has built by using realist perspective of international relations and supported by security theories. This research also using nation-state as the level of analyze which aimed on strategies by Saudi Arabia on it own government stability. Formulation of facts, data, arguments, theoretical framework in this research using qualitative explanation methods. Focus on this research is Saudi Arabia’s strategies in order to defending it own government stability during Arab Spring and explain stability of Saudi Arabia government.This research has formulated answer-hypothesis which revealed the fact of ability of Saudi Arabia government to remains stable is by it’s strategies to minimalyze factor of revolution and policy to maintain social stabilization. According to the strategy, Arab Saudi remains as a stable nation and government with no change in the nation nor the government. This fact can be proved by ability of Arab Saudi to supported other middle east countries by security support and economical supportKeywords : Strategies, policies, government, security, stability, Saudi Arabia, Arab Spring, Middle East